Analysis of Psychosocial Adjustment in the Family During Confinement: Problems and Habits of Children and Youth and Parental Stress and Resilience - Andrés-Romero, Magdalena P.; Flujas-Contreras, Juan M.; Fernández-Torres, Mercedes; Gómez-Becerra, Inmaculada; Sánchez-López, Pilar (Frontiers in Psychology, 2021)
The COVID-19 health crisis has led to a dramatic change in dynamics and habits of families, which may be a factor involved in the development and maintenance of problems and difficulties in children. The present study is a cross-sectional study that aims to describe and analyze the relationship between the difficulties in psychological adjustment and the change of habits of the infant-juvenile population as perceived by their parents and their stress and resilience during the total confinement of the first wave of the COVID-19 pandemic in Spain, as well as analyzing the course of the changes and the relationships between weeks 3 to 6, that is, the score of different participants in each week of the confinement. The sample is comprised of 883 parents of children and adolescents between 3 and 18 years of age. Children’s psychological adjustment, children’s habits, parental stress, and parental resilience were assessed by parents. The results show that parents perceive a change in the habits and psychological difficulties in their children. At the same time, our results describe parents with a high level of stress and resilience, with differences depending on the children’s ages. The time of confinement accentuates the perception of parents about the psychological difficulties of their children and parental stress, as well as a decrease in resilience. These difficulties are reduced when the parent has resilience competencies. These results show that the resilience of parents mediate the relationship between parental stress and psychological problems of their children. These results shows that COVID-19 lockdown had a considerable effect on families, both on children and parents. Some practical implications based on results are provided.